Analisis Aspek-aspek Keberhasilan Pembelajaran di Indonesia: Ditinjau dari Studi Observasi - Deasy Yunita Siregar; Lutfi Putri Khairani; Sonia Sabilla; Yusriani Yusriani; Rizki Putri Jasmine Siahaan (Tarbiatuna: Journal of Islamic Education Studies, 2024)
The importance of this research lies in its contribution to the development of educational policy, the formulation of more effective teaching strategies, and the provision of direction to educational practitioners. By better understanding the factors that influence learning success, it is hoped that this research can become a valuable guide in improving the quality of education in Indonesia so that it meets global demands and prepares future generations optimally. Observational analysis research is a research approach in which researchers make direct observations of certain phenomena or events to gain a deeper understanding. In this context, "observational analysis" refers to the process of analyzing data obtained through direct observation. This method is usually used to explore in-depth information about behavior, interactions, or certain situations in the natural environment. Observational analysis research is often adopted in the fields of psychology, sociology, anthropology and education (Moleong, 2010). Based on the description of the research background related to the analysis of aspects of successful learning in Indonesia through observational studies, it can be concluded that education in Indonesia faces complex and diverse challenges. Several obstacles, such as regional disparities, varying teacher quality, access to technology, and the role of parents in education, provide a context that requires serious attention.